Nineteenth-Century Lutheran Theologians: . ELib - Becker, Matthew L.; Frank, Günter; Lotz-Heumann, Ute; Mahlmann-Bauer, Barbara; Schilling, Johannes; Wassilowsky, Günther; Westphal, Siegrid; Rasmussen, Tarald; Lamberigts, Mathijs; Gordon, Bruce; Whitford, David M. ca. 20./21. Jh.; Helmer, Christine; et al. (Refo500 Academic Studies (R5AS)., 2015)
Angaben zur beteiligten Person Mattes: Mark Christopher Mattes, Ph.D., is Professor of Philosophy and Religion at the Grand View University in Des Moines, Iowa, USA.